Pengaruh Lokasi Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian di Toko Nanda Mart Masamba - Septiningsi, Emah; M. Suhardi, Anwar; Hasbi, Andi Rizkiyah (Universitas Nusantara PGRI Kediri, 2023)
T The purpose of this study is to discuss, analyze, and articulate the importance of location, price, and service quality in relation to customer complaints. Location, cost, and service quality are the main variables in this article. On the other hand, the dependent variable in this research article is purchasing decisions. This study belongs to descriptive analytic research using a quantitative method. The population in the study consists of customers who have shopped at Nanda Mart Masamba Store. Since the population size is not directly known, a sample size of 180 respondents was taken using non-probability sampling technique, including 1) customers of Nanda Mart Masamba Store, and 2) minimum age of 18 years old. The analysis method used in this study is linear regression, with t-test and F-test as the data analysis techniques. The research findings indicate that location has a significant partial influence on purchasing decisions at Nanda Mart Masamba Store. This means that a good or strategic location can influence customers' decisions to make purchases at the store. However, the study also reveals that price, although it has an influence on purchasing decisions, is not statistically significant. This implies that price is not the main factor influencing customers' purchasing decisions at the store. Additionally, the study finds that service quality has a significant influence on purchasing decisions at Nanda Mart Masamba Store. Good and quality services can enhance customer trust and encourage them to make purchases at the store. Overall, location, price, and service quality play a positive and significant role in influencing purchasing decisions at Nanda Mart Masamba Store. These factors require attention and improvement to enhance customer satisfaction and boost sales at the store.